2004
DOI: 10.1161/01.cir.0000139844.15045.f9
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Chronic Pharmacological Manipulation of β-Adrenoreceptor Subtype Signaling in Rodent Dilated Ischemic Cardiomyopathy

Abstract: Background-Studies in isolated cardiac myocytes have demonstrated that signaling via specific ␤ 1 -adrenergic receptor subtypes (␤ 1 ARs) promotes but that signaling via ␤ 2 ARs protects from cell death. We hypothesized that prolonged ␤ 2 AR stimulation or ␤ 1 AR blockade would each protect myocytes from death and thereby ameliorate cardiac remodeling in chronic heart failure. Methods and Results-A large myocardial infarction (MI) induced in rats by coronary artery ligation resulted in a dilated cardiomyopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
95
3
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 31 publications
15
95
3
3
Order By: Relevance
“…For example, ␤AR stimulation, through PKA activation, phosphorylates PLB, which disinhibits sarcoplasmic reticulum Ca 2ϩ ATPase and facilitates Ca 2ϩ uptake into the sarcoplasmic reticulum, increasing cardiac function (57). However, sustained ␤AR activation is associated with cardiac myocyte apoptosis (58,59), which is not seen in animals expressing nuclear Akt (40) or AC VI (56). Reduction of PLB through antisense suppression or genetic ablation increases sarcoplasmic reticulum calcium cycling and increases cardiac function (60,61), and cardiac-directed expression of PLB decreases heart function (62).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ␤AR stimulation, through PKA activation, phosphorylates PLB, which disinhibits sarcoplasmic reticulum Ca 2ϩ ATPase and facilitates Ca 2ϩ uptake into the sarcoplasmic reticulum, increasing cardiac function (57). However, sustained ␤AR activation is associated with cardiac myocyte apoptosis (58,59), which is not seen in animals expressing nuclear Akt (40) or AC VI (56). Reduction of PLB through antisense suppression or genetic ablation increases sarcoplasmic reticulum calcium cycling and increases cardiac function (60,61), and cardiac-directed expression of PLB decreases heart function (62).…”
Section: Discussionmentioning
confidence: 99%
“…18 In a rat model of myocardial infarction, treating with β2-AR agonists for 2 weeks preserved cardiac contractility and reduced the number of apoptotic cardiomyocytes. 19 The β3-AR expression is upregulated in the failing heart. 20 It is reported that β3-AR negatively modulates ventricular contractility by activating endothelial nitric oxide synthase.…”
Section: β-Ar-mediated Apoptosis Of Cardiomyocytesmentioning
confidence: 99%
“…Accordingly, it has been suggested that chronic treatment with β 2 AR-agonists might exert beneficial effects in CHF (48). In fact, Ahmet et al have recently shown that in rats with ischemic cardiomyopathy (ICM) due to myocardial infarction, longterm treatment with the β 2 AR-agonists zinterol and fenoterol exerted beneficial effects (attenuation of disease progression) that were mainly due to their antiapoptotic effects (49). However, before extrapolating from these data obtained in rats with experimental heart failure to the human situation, the following caveats should be considered: a) while zinterol appears to belong to those β 2 AR-agonists that can signal via the G s -and G i -protein pathway, fenoterol has been shown by two different groups to signal selectively via the G s -protein pathway (see above).…”
Section: Role Of Changes In G I -Proteinmentioning
confidence: 99%